Hydrothermal Synthesis and Crystal Structure of Hexaaqua-Zinc(II) 5-Nitro-benzene-1,2,3-tricarboxylic Acid - Li, S.H.; Fu, W.J. (Asian Journal of Chemistry, 2014)
A new zinc complex with the formula Zn(C18H28N2O26) is formed by reacting Zn(OAc)2.2H2O with 5-nitro-benzene-1,2,3-tricarboxylic acid. The compound has been characterized by X-ray single-crystal diffraction, compound shows a one-dimensional framework. The 1D supramolecular structure is formed via hydrogen bonding connection.